Portable Prisons: Electronic Monitoring and the Creation of Carceral Territory - Gacek, James (McGill-Queen's University Press, 2022)
Portable Prisons is an exploration of the electronic monitoring of offenders based on an ethnographic case study from Scotland. Through interviews and observations, Gacek demonstrates this technology is representative of the carceral state's overreaching punitive capabilities, rejecting the idea that "soft" punishment is related to decarceration.